Ekolinguistik dalam Pendidikan Bahasa Indonesia: Pengaruh Perubahan Lingkungan terhadap Keterampilan Berbahasa - Kholid, Kholid; Maimun, Muhamad (CT. Rajawali media Utama, 2023)
This research explores the concept of ecolinguistics in the context of Indonesian language education with a focus on a review of environmental change and its impact on language skills. The ever-changing environment plays a significant role in language teaching and learning, resulting in the evolution of teaching methods and skills required in the era of globalization. This research uses a qualitative approach with a case The results of the analysis highlighted the role of technology, socio-cultural changes, and other environmental factors in shaping new needs and demands in language skills. It was found that environmental changes affect listening, speaking, reading and writing skills in Indonesian language learning. Technology provides new opportunities, while globalization demands broader language skills. This research also identifies innovations in Indonesian language teaching methods that are responsive to environmental changes. The application of technology, project-based learning and socio-cultural engagement are key elements in improving teaching effectiveness. The research highlights the challenges faced by educators in adapting their teaching methods. These challenges involve the need to keep abreast of technological developments, understand socio-cultural dynamics and design adaptive curricula.